2010
DOI: 10.1088/0022-3727/44/2/025202
|View full text |Cite
|
Sign up to set email alerts
|

Measured density of copper atoms in the ground and metastable states in argon magnetron discharge correlated with the deposition rate

Abstract: Abstract:In a dc-magnetron discharge with argon feed gas, densities of copper atoms in the ground state Cu( 2 S 1/2 ) and metastable state Cu*( 2 D 5/2 ) were measured by resonance absorption technique, using a commercial hollow cathode lamp as light source. The operating conditions were 0.3 -14 µbar argon pressure and 10 -200 W magnetron discharge power. The deposition rate of copper in a substrate positioned at 18 cm from the target was also measured with a quartz microbalance. The gas temperature, in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Also, the density of the sputtered particles is much lower than the density of the noble working gas. 65 The primary mechanism for the ionization of the sputtered metal vapor in a dcMS is Penning ionization through impact with the working noble gas atoms that are in the metastable state. 66 The mean free path for the sputtered vapor with respect to electron impact ionization is over 50 cm.…”
Section: -63mentioning
confidence: 99%
“…Also, the density of the sputtered particles is much lower than the density of the noble working gas. 65 The primary mechanism for the ionization of the sputtered metal vapor in a dcMS is Penning ionization through impact with the working noble gas atoms that are in the metastable state. 66 The mean free path for the sputtered vapor with respect to electron impact ionization is over 50 cm.…”
Section: -63mentioning
confidence: 99%
“…The remaining light from HCL together with the light produced by Cu atoms inside the vacuum chamber after passing the 35 cm tube (9) enters the monochromator (10), through a second quartz lens with 5 cm focal distance. The spectral light is separated inside the monochromator from other lights and enters the photomultiplier tube (11). The detector counts the number of arriving photons and sends counts via RS-232 interface to the computer (12).…”
Section: Methodsmentioning
confidence: 99%
“…Thus the gas temperature is measured via N 2 molecule rotational emission light. The result of the measured variation of the number density with the input power and for three different pressures (0.3 µbar, 4.5 µbar and 14 µbar) are given in the reference 10,11 for Cu atoms in ground state and also in metastable state. For the ground state of Cu, the 327.4 nm line and for the metastable state the 510.6 nm lines are used.…”
Section: Methodsmentioning
confidence: 99%
“…Sasaki et al 10 have suggested that dimmers and trimmers of Fe, Ti, and Cu atoms can also be sputtered from metallic targets and dissociated in the phase gas. Furthermore, Naghshara et al 11 have reported the Cu-atom densities in the ground and metastable states using resonance absorption technique. These studies concluded that the sputtered atoms from the target are almost in ground state and get excited or ionized later in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for Cu deposition, both metastable and ground-state Cu atoms were shown to contribute significantly to the plasma deposition rate on the substrate. 11 Because of their high carrier concentrations and high optical transmittance in the visible and near infrared, ZnO-based thin films and nanomaterials are very attractive for many applications, 12,13 including flexible electronics, 14,15 optoelectronics, 16 solar cells, 17,18 and sensors. 19 While the literature is abundant on the evolution of the film properties and their various applications, much less efforts were devoted to fundamental investigations of sputtered species and their transport properties during magnetron sputtering of technologically relevant targets such as ZnO and their alloys.…”
Section: Introductionmentioning
confidence: 99%